Literasi Digital Bijak Bermedia Sosial Di Desa Kaliangkrik - Randyantokho Randyantokho; Meita Anindya Safitri; Sukmawati Waluyo Putri; Lia Oktavya Susilo Putri; Rizal Adiyatma; Lailatul Fitria; Kartika Damayanti; Laelatul Aina Fadhilah; Aulia Ines Mubiarto; M Fadhil Zaeruki; Muhammad Fachrie (Pusat Riset dan Inovasi Nasional, 2024)
Wise literacy in social media is a critical aspect in dealing with the complexity of online interactions in the digital era. A deep understanding of social media-platform use and the ability to critically evaluate information is at the core of this literacy. Individuals who have wise social media literacy can filter out inaccurate information, understand the social, cultural and political impacts of the content they consume or share. The importance of wise social media literacy also involves responding to disinformation, where individuals can effectively avoid the spread of fake or manipulative news. Ethical aspects of communication are also a focus, with this literacy teaching individuals to promote healthy dialogue and respect diversity of opinion, forming a more positive and inclusive online environment. This research aims to find out how the pattern of community service is a manifestation of the tridharma of higher education related to aspects of community service. In implementing the community service program that has been prepared previously, the method used is increasing knowledge by means of counseling or socialization with the aim of providing understanding and wise skills in digital literacy from the extension team. Apart from that, wise social media literacy also considers online security and privacy risks. Users need to be able to manage and protect their personal information, avoid threats such as fraud, and carefully guard their digital identity. This is not only an individual skill, but also a contribution to the sustainability and security of the global digital environment. By mastering social media literacy, individuals can better navigate the complexities of social media, participate positively, and make informed and wise decisions in using these platforms. Overall, smart social media literacy is an important foundation for forming individuals who are able to interact wisely in an ever-growing digital world. By combining an understanding of content, communication skills, and awareness of security risks, wise social media literacy helps shape an intelligent, ethical, and empowered online society.